Quantum mechanics : - Peleg, Yoav (McGraw-Hill, 2006)
Pared-down, simplified, and tightly focused, Schaum’s Easy Outline of Quantum Mechanics is perfect for anyone turned off by dense text. Cartoons, sidebars, icons, and other graphic pointers get the material across fast, and concise text focuses on the essence of quantum mechanics. This is the ideal book for last-minute test preparation and for expert tops for mastering quantum mechanics.